2012
DOI: 10.1200/jco.2012.30.15_suppl.3011
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of selective cyclin dependent kinase inhibitor P1446A-05 administered on an intermittent schedule in patients with advanced refractory tumors.

Abstract: 3011 Background: Cyclin-dependent kinases (Cdks) have emerged as important targets in anticancer drug development. P1446A-05 is a potent and specific inhibitor of Cdk4-D1 (IC50-0.09µM), Cdk1-B (IC50-0.025µM), and Cdk9-T (IC50-0.022µM). This study was designed to determine the maximum tolerated dose (MTD), dose limiting toxicity (DLT), safety profile, pharmacokinetics, and antitumor activity of orally administered P1446A-05 in patients with advanced refractory tumors. Methods: This study was conducted at 5 cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…P1446A inhibits CDK1, 2, 4, 5, 6, 8 and 9 with IC 50 values of at 25, 180, 90, 210, 210, 12 and 22 nmol/L, respectively (S1 Fig) . P1446A induced cell cycle arrest and apoptosis of solid tumor cell lines in vitro and restricted growth in human colon (HCT-116) and non-small cell lung (H-460) carcinoma xenograft mouse models (Piramal Healthcare Ltd., proprietary information; [24]). Furthermore, P1446A showed promising activity in two independent Phase I clinical trials in patients with solid tumors [25,26]. Here we demonstrate that P1446A inhibits CDK activity and induces rapid apoptosis in peripheral blood CLL cells.…”
Section: Introductionmentioning
confidence: 60%
“…P1446A inhibits CDK1, 2, 4, 5, 6, 8 and 9 with IC 50 values of at 25, 180, 90, 210, 210, 12 and 22 nmol/L, respectively (S1 Fig) . P1446A induced cell cycle arrest and apoptosis of solid tumor cell lines in vitro and restricted growth in human colon (HCT-116) and non-small cell lung (H-460) carcinoma xenograft mouse models (Piramal Healthcare Ltd., proprietary information; [24]). Furthermore, P1446A showed promising activity in two independent Phase I clinical trials in patients with solid tumors [25,26]. Here we demonstrate that P1446A inhibits CDK activity and induces rapid apoptosis in peripheral blood CLL cells.…”
Section: Introductionmentioning
confidence: 60%
“…Since target profiling studies revealed CDK9 as a main target of voruciclib, we next assessed the impact of voruciclib on MCL-1 expression in cell-based and xenograft models of DLBCL. To understand whether clinically achievable and tolerated levels of voruciclib repress MCL-1, we used existing pharmacokinetic data from the two completed Phase 1 trials to model expected plasma drug levels achieved upon dosing with a conservative regimen of 250 mg/day voruciclib 26 , 27 . (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here we demonstrate that the small molecule flavone derivative, voruciclib, a clinical stage CDK inhibitor, targets CDK9 with sub-nanomolar biochemical potency and represses expression of MCL-1 in multiple models of DLBCL. The safety profile and tolerability of voruciclib has been established by two independent Phase 1 clinical trials 26 , 27 . Furthermore, voruciclib is distinguished from other CDK9 inhibitors such as flavopiridol or dinaciclib by its oral bioavailability, making it an exceptionally attractive candidate for clinical development.…”
Section: Introductionmentioning
confidence: 99%
“…It was studied in 10 other clinical trials; however, it is currently not under active development. Voruciclib (P1446A‐05, 73 ) is a structural analog of P276‐00 that inhibits CDK9 (IC 50 = 22 nM) and is orally bioavailable 213–216 . It displays potent antiproliferative activity across 30 cancer cell lines, including prostate, colon, and lung cancer cells 215 .…”
Section: Cdk Inhibitors In Clinical and Preclinical Pipelinementioning
confidence: 99%